Regional Accreditation Standards and Contingent and Part‐Time Faculty. Issue 176 (25th March 2018) - Pham, Nhung; Osland Paton, Valerie
Abstract: Accreditation demonstrates an institution's commitment to quality academic experiences for their students and consistent institutional development. This chapter discusses the role of contingent faculty in the accreditation process.